Розробка підсилювача потужності звукової частоти - Таран, О. С. (ХНУРЕ, 2021)
By using multiple speakers in a speaker system that reproduce specific ranges of sound frequencies, the sound quality can be improved to a great extent, which is not the case for a single-way system. In this case, you can use passive filters after the low-frequency power amplifier, but this solution is less effective than a system in which each speaker has its own active filter and amplifier. In the latter case, we get a significant reduction in power loss and an increase in sound quality, due to better stage matching and the use of operational amplifiers in active filters.
Keywords: підсилювач потужності звукової частоти; розробка підсилювача потужності